2014
DOI: 10.7603/s40632-014-0002-3
|View full text |Cite
|
Sign up to set email alerts
|

The modeling of oxygen transfer efficiency in gated conduits by using genetic expression programming

Abstract: Oxygen transfer is the process by which oxygen is transferred from the gaseous to the liquid phase. The oxygen transfer efficiency depends almost entirely on the amount of surface contact between the air and water. This surface contact can be increased by gated conduits that involve air-water mixture flow. In reality, the physical structure of the air-water interface is complex and still awaits clarification. In recent years, different soft computing systems have been successfully employed for the solution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that injecting air into the flow downstream of the gate can significantly reduce the risk of cavitation damage. The air-demand ratio and the aeration efficiency in gated closed conduits have been investigated by Aydin et al (2021Aydin et al ( , 2022Aydin et al ( , 2023, Baylar and Batan (2010), Baylar et al ( , 2021Baylar et al ( , 2022, Campbell and Guyton (1953), Haindl and Sotornik (1957), Hohermuth (2017Hohermuth ( , 2019, Hohermuth et al (2020), Kalinske and Robertson (1943), Mortensen (2009), Mortensen et al (2011Mortensen et al ( , 2012, Mortensen and Kubitschek (2016), Oveson (2008), Ozkan et al (2006aOzkan et al ( , 2006bOzkan et al ( , 2010Ozkan et al ( , 2014Ozkan et al ( , 2015, Rajaratnam (1962), Safavi et al (2008), Sharma (1976), Speerli (1999), Speerli and Hager (2000), Tuna et al (2014), Unsal et al (2008Unsal et al ( , 2009Unsal et al ( , 2014, USACE (1964), Wisner (1965).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that injecting air into the flow downstream of the gate can significantly reduce the risk of cavitation damage. The air-demand ratio and the aeration efficiency in gated closed conduits have been investigated by Aydin et al (2021Aydin et al ( , 2022Aydin et al ( , 2023, Baylar and Batan (2010), Baylar et al ( , 2021Baylar et al ( , 2022, Campbell and Guyton (1953), Haindl and Sotornik (1957), Hohermuth (2017Hohermuth ( , 2019, Hohermuth et al (2020), Kalinske and Robertson (1943), Mortensen (2009), Mortensen et al (2011Mortensen et al ( , 2012, Mortensen and Kubitschek (2016), Oveson (2008), Ozkan et al (2006aOzkan et al ( , 2006bOzkan et al ( , 2010Ozkan et al ( , 2014Ozkan et al ( , 2015, Rajaratnam (1962), Safavi et al (2008), Sharma (1976), Speerli (1999), Speerli and Hager (2000), Tuna et al (2014), Unsal et al (2008Unsal et al ( , 2009Unsal et al ( , 2014, USACE (1964), Wisner (1965).…”
Section: Introductionmentioning
confidence: 99%